1999
DOI: 10.1074/jbc.274.32.22517
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase II-deficient Mice

Abstract: Type 2 diabetes is characterized by decreased rates of insulin-stimulated glucose uptake and utilization, reduced hexokinase II mRNA and enzyme production, and low basal levels of glucose 6-phosphate in insulin-sensitive skeletal muscle and adipose tissues. Hexokinase II is primarily expressed in muscle and adipose tissues where it catalyzes the phosphorylation of glucose to glucose 6-phosphate, a possible rate-limiting step for glucose disposal. To investigate the role of hexokinase II in insulin action and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 49 publications
0
24
1
Order By: Relevance
“…Although there are no data in humans with type 1 diabetes, studies done in obese and type 2 diabetic patients have shown similar findings (5,24,25). Mice with a heterozygous knockout of hexokinase II have a 50% decrease in hexokinase II mRNA and a corresponding 50% decrease in muscle glucose uptake, suggesting that hexokinase II may serve as a rate-limiting step for glucose uptake in the muscle (26). The second irreversible and rate-limiting step in glycolysis is the conversion of fructose 6-phosphate to fructose 1,6-bisphosphate and is catalyzed by phosphofructokinase-1 (PFK-1).…”
Section: Resultsmentioning
confidence: 56%
“…Although there are no data in humans with type 1 diabetes, studies done in obese and type 2 diabetic patients have shown similar findings (5,24,25). Mice with a heterozygous knockout of hexokinase II have a 50% decrease in hexokinase II mRNA and a corresponding 50% decrease in muscle glucose uptake, suggesting that hexokinase II may serve as a rate-limiting step for glucose uptake in the muscle (26). The second irreversible and rate-limiting step in glycolysis is the conversion of fructose 6-phosphate to fructose 1,6-bisphosphate and is catalyzed by phosphofructokinase-1 (PFK-1).…”
Section: Resultsmentioning
confidence: 56%
“…An alternative approach is to increase the resistance to a step by genetically lowering the concentration or functional activity of those same proteins and determine whether such a manipulation reduces MGU. This was done for glucose phosphorylation by partially knocking out HK II (25,26), and it was demonstrated that glucose phosphorylation is a primary site of resistance to MGU during exercise, because partial HK II knock-out mice had impaired glucose influx in oxidative muscles (26). Here we show that a partial GLUT4 ablation in C57BL/6J mice impaired neither sedentary nor exercise-stimulated MGU in any of the muscles studied at 4 months of age.…”
Section: Discussionmentioning
confidence: 84%
“…The HK +/- mice were first described by Heikkinen et al [12] and have a partial deletion to the HKII gene; the HK tg mice contain a HKII transgene composed of the human HKII cDNA driven by the rat muscle creatine kinase promoter [2]. HK +/- and HK tg were initially bred with wild-type C57Bl/6 mice (Jackson Laboratories) and subsequently by wild-type offspring, which were used for this investigation.…”
Section: Methodsmentioning
confidence: 99%
“…To study alterations in the level of HK, we make use of two different HKII genotypes: the C57Bl/6 mice with a partial deletion of HKII [12; HK +/- ] as well as mice overexpressing HKII (HK tg ) [2]. These mice are reported to have a 50% decrease (HK +/- ) and a 350% increase (HK tg ) in HKII content relative to wild-type (WT) gastrocnemius muscles [8].…”
Section: Introductionmentioning
confidence: 99%